ANALISIS SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN PADA TRANSPORTASI UMUM BUS EFISIENSI (PO. EFISIENSI RUTE YOGYAKARTA, PURWOKERTO, PURBALINGGA, DAN CILACAP) - Winda Pangesti; Hendro Setyono (Universitas Ahmad Dahlan, 2016)
This research has a purpose to know the influence of five dimension of service quality that is, Reliability, responsivness, assurance, emphaty, and tangible may affect statification bus route Efisiensi Yogyakarta, Purwokerto, Purbalingga dan Cilacap. Quantitative type research. Sampling with purposive sampling that has the minimum criteria ever ride bus 2 times. Data collection used questionnaries with validity and reliability testing, in the data analysis using multiple regression analysis, t test, f test, and R square. the subjects of this research are the pasanggers of the bus Efisiensi of Yogyakarta route, Purwokerto, Purbalingga, and Cilacap. The result of the study 1) reliability affect consumer statifications 2) responsivnes does not affect costumer statifications 3) assurance affect costumer statifications 4) emphaty affect costumer statifications and 5) tangible affect to costumer statifications. Together, reliability, assurance, responsivness, emphaty and tangible have a significant effect on statifications. By regression equations Y = 0,387 + 0,260X1 – 0,003 X2 + 0,251 X3 + 0,198 X4 + 0,226X5. R square of 0,639 or 63,9% is influential and the remaining 36,1% is influenced by other variabels that are not in the research.